Transição das razoes trigonométricas do triângulo retângulo para o círculo trigonométrico: uma sequencia para o ensino - Borges, Carlos Francisco (2009)
The purpose of this essay was to contribute to Trigonometry teaching, specially, to the transition of the trigonometric reasons in the rectangle triangle for the trigonometric circle. A sequence was elaborated with 12 activities, from which ten were created worrying about guiding the student to understand the trigonometric reasons of the rectangle triangle to the trigonometric circle using the dynamic geometry software Geogebra. An activity was made with the objective of working with the radian definition and the conversion of the unit circle (radians) to the angle unit (degrees) and, at last, an activity which had as purpose to create a tool to be used in the classroom when it was not possible to use the calculator, or the computer. The activities were applied to 12th graders in a school from the city of Francisco Morato, Great São Paulo. For such, 4 meetings were used to do the application; the students did the activities in pairs and were not done during the lessons. The Theory of the Didactic Situations and other basis of the Didactic Engineering were used in the elaboration, analysis, application and data survey of the teaching sequence. The experimentation pointed that the students did not make use of some necessary previous knowledge and presented some difficulties to expose their written observations. However, it also showed that there was improvement in the students learning, because while doing the activities using the dynamic geometry, they showed interest and focus